Análise comparativa da utilização de reservatórios individuais no sistema de drenagem urbana para detenção de cheias em contrapartida ao sistema convencional - Neves, Ândrio Matheus Colomby das (2017)
Due to the process of urbanization and its impacts, such as the increase of soil sealing, which is responsible for most of changes in surface runoff, it is necessary to seek reliable measures for the management of urban drainage, in order to avoid problems caused by an inefficient direction of rainwater. The concept of channeling and rapid downstream volume flow still prevails over other more sustainable and possibly more effective methods, causing several problems that are transferred to other places rather than actually solving them. Thus, an understanding of the need to adopt an alternative rainfall drainage system that are able to control the urbanization process problems is essential. Seeking to reduce the peak flow, this paper presents a comparison between the size factors and the budget of two drainage network possibilities. Where the first method considered is the traditional plumbing concept, and in the second one, the application of an individual detention reservoir in each portion of a site destined to industries development in the city of Vitorino – PR. At the end of this analysis, it is necessary to consider that the economic aspect should not be the only factor making the use of an alternative drainage system impossible, since in some situations the damage caused by an inefficient system can bring more costly further consequences.